DEVELOPING STUDENTS’ CREATIVE POTENTIAL THROUGH INDIVIDUALIZED APPROACHES - Rahmatova Aziza Ahmatovna, (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This article explores the use of individualized approaches to develop students’ creative potential in visual arts education. It examines pedagogical strategies that cater to each student’s unique abilities, learning pace, and artistic preferences. By providing personalized guidance, differentiated tasks, and supportive feedback, educators can foster creativity, self-expression, and critical thinking. The study also highlights the role of motivation, reflection, and tailored exercises in helping students realize their full artistic potential.